Integrating Historical Awareness into High School History Learning - Bety Diana Serly Hethario; Muhammad Hanif; Johan Setiawan; Ninik Sudarwati (Ta'dib)
This study aims to analyze (1) the reality of history learning, (2) the efforts of teachers in fostering historical awareness in history learning, and (3) the supporting and inhibiting factors in instilling historical awareness through history education. This research employs a qualitative method with a phenomenological approach and is presented through descriptive analysis. The subjects of the study are history teachers and students at SMAN 6 Metro. Data collection techniques include interviews, observations, and documentation. The research findings show that: (1) history learning at SMAN 6 Metro is based on the independent Curriculum, and teachers apply various teaching methods and media suited to the material being taught; (2) teachers promote historical awareness by using historical content that includes values of nationalism and patriotism, building direct engagement with students, applying innovative and effective teaching methods, and organizing field trips or historical excursions; and (3) supporting factors include the professionalism of history teachers, while inhibiting factors include incomplete school facilities, the lack of a history laboratory, unsupportive student attitudes, and limited time allocation for history learning. Based on these findings, it is recommended that schools improve the facilities that support history education, provide further training for history teachers, and ensure sufficient time allocation for teaching history.